A minimal resting time of 25 min is needed before measuring stabilized blood pressure in subjects addressed for vascular investigations. Issue 1 (December 2017) - Mahe, Guillaume; Comets, Emmanuelle; Nouni, Aziz; Paillard, François; Dourmap, Caroline; Le Faucheur, Alexis; Jaquinandi, Vincent
Abstract Blood pressure (BP) measurement is a central element in clinical practice. According to international recommendations 3 to 5 minutes of resting is needed before blood pressure measurement. Surprisingly, no study has modelled the time course of BP decrease and the minimum resting-time before BP measurement. A cross-sectional bicentric observational study was performed including outpatients addressed for vascular examination. Using two automatic BP monitors we recorded the blood pressure every minute during 11 consecutive minutes. The data was analyzed by non-linear mixed effect regression. Systolic (SBP) and diastolic BPs were studied and we tested the effect of covariates on its evolution through log-likelihood ratio tests. We included 199 patients (66+/−13years old). SBP was found to decrease exponentially. Simulations based on the final model show that only half the population reaches a stabilized SBP (defined as SBP + 5 mmHg) after 5 min of resting-time while it takes 25 min to ensure 90% of the population has a stabilized SBP. In conclusion, our results and simulations suggest that 5 minutes are not enough to achieve a stabilized SBP in most patients and at least 25 minutes are required. This questions whether the diagnosis of hypertension can be reliably made during routine visits in general practitioners' offices.